Variation in Petal and Leaf Wax Deposition Affects Cuticular Transpiration in Cut Lily Flowers - Cheng, Guiping; Wang, Ling; Wu, Hairong; Yu, Xinfan; Zhang, Nan; Wan, Xiaorong; He, Lihong; Huang, Hua (Frontiers in Plant Science, 2021)
The vase life of cut flowers is largely affected by post-harvest water loss via the petals. Cuticular wax is the primary barrier to uncontrolled water loss from aerial plant organs. Studies on leaf cuticular transpiration have been conducted; however, little is known about cuticular transpiration in flowers. Here, the cuticular transpiration rate and wax composition of three lily cultivars were determined. The minimum water conductance of tepal cuticles was higher at the green bud than open flower stage. Lily cuticular transpiration exhibited cultivar- and organ-specific differences, where transpiration from the tepals was higher than leaves, and higher in the ‘Huang Tianba’ than ‘Tiber’ cultivar. The overall wax coverage of the tepals was higher compared to that of the leaves. Very-long-chain aliphatics were the main wax constituents, and were dominated by n-alkanes with abundant carbon chain lengths of C27 and C29, and C29 and C31 in the tepal and leaf waxes, respectively. Abundance of primary alcohols and fatty acids as well as small amounts of alkyl esters, ketones, and branched or unsaturated n-alkanes were also detected in both tepal and leaf waxes, depending on the cultivar and organ. In addition, the chain-length distributions were similar between compound classes within cultivars, whereas the predominant carbon chain lengths were substantially different between organs. This suggest that the less effective transpiration barrier provided by the tepal waxes may result from the shorter carbon chain aliphatics in the tepal cuticle, compared to those in the leaf cuticle. These findings provide further insights to support the exploration of potential techniques for extending the shelf-life of cut flowers based on cuticular transpiration barrier properties.